2017
DOI: 10.1002/ets2.12177
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Using TOEIC® Test Scores to Inform Human Resource Management Decisions

Abstract: This report explores the ways in which human resource (HR) managers use TOEIC® scores to inform hiring, promotion, and training decisions in an international workplace. Two data sources were used (a) previously collected test users' testimonials that described managers' use of TOEIC scores to inform HR decisions and (b) test‐use examples collected from HR managers and TOEIC representatives specifically for this project. Our analysis of test‐use examples provided insight into how companies use TOEIC scores to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…To date, however, there is no empirical research that investigates altogether the relationship among IDLE practice, high-stakes international English test (TOEIC scores), English productive levels (English speaking and productive vocabulary levels), and EIL perceptions among contemporary EFL learners. In addition, while prior research has reported a link between TOEIC score and IDLE practice (Lee, 2019;Tagashira et al, 2010), IDLE practice and EIL perception (Lee & Lee, 2019a, 2019b, and TOEIC score and EIL perception (Oliveri & Tannenbaum, 2017), it remains to be seen whether IDLE practice plays a mediating role in the relationship between TOEIC scores and perceptions of EIL. The current study aimed to address these research gaps in the literature.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…To date, however, there is no empirical research that investigates altogether the relationship among IDLE practice, high-stakes international English test (TOEIC scores), English productive levels (English speaking and productive vocabulary levels), and EIL perceptions among contemporary EFL learners. In addition, while prior research has reported a link between TOEIC score and IDLE practice (Lee, 2019;Tagashira et al, 2010), IDLE practice and EIL perception (Lee & Lee, 2019a, 2019b, and TOEIC score and EIL perception (Oliveri & Tannenbaum, 2017), it remains to be seen whether IDLE practice plays a mediating role in the relationship between TOEIC scores and perceptions of EIL. The current study aimed to address these research gaps in the literature.…”
Section: Introductionmentioning
confidence: 90%
“…The current ETS official home page also asserts that people who take TOEIC tests can demonstrate "[their] English communication skills needed in today's global workplace ... organizations can be confident they are using a test that measures a range of skills relevant and necessary for success in global workplace communications" (ETS, 2018c). Employers in multinational businesses, such as Shanghai Expo in mainland China (Oliveri & Tannenbaum, 2017) and multinational military units, such as the Joint Security Area between North and South Korea (International Communication Foundation, 2005) have adopted TOEIC tests to select potential professionals who have global mindsets and who seek to improve their cross-cultural communication skills.…”
Section: High-stakes International English Tests and Eilmentioning
confidence: 99%
See 2 more Smart Citations
“…Research is critical for supporting claims about the measurement quality and intended use of tests, but all test developers have limited resources. Based on critical evaluations of fully specified TOEIC AUAs, one area of research that the TOEIC program has pursued over the last several years has been focused on the uses of TOEIC tests and their potential impact on various stakeholder groups; several chapters in the third edition of the TOEIC Compendium address these focal issues (e.g., Hsieh, ; Oliveri & Tannenbaum, ).…”
Section: Uses Of Validity Arguments For Toeic Testsmentioning
confidence: 99%